Relationship Between Nutritional Status With The Development of Toddlers (Age 1-5 Years) in The Work Area of The Candi Sidoarjo Community Health Center - Perdana, Dimas Anugerah; Maimunah, Siti; M. Afif Hilmi (Global Ten Public Health and Nursing Journal, 2024)
Infants Are A Very Important Stage In Life And Special Attention Is Needed During This Period. Various Factors Including Lack Of Nutritional Intake, Proper Parenting, Economic Crisis, Lack Of Knowledge, And Lack Of Sanitation And Basic Health Services, Affect The Poor Nutritional Status Of Young Children. Poor Nutritional Status Can Result In Developmental Disorders. This Study Aims To Determine The Relationship Between Nutritional Status And The Growth And Development Of Early Childhood (Ages 1–5 Years).Research Method: This Study Uses A Correlation Study Method Using A Cross-Sectional Approach Involving 45 Toddler Respondents In The Candi Sidoarjo Health Center Working Area Selected Through Purposive Sampling Techniques. Data Collection Was Carried Out Using Anthropometric Measurements And Screening In Assessing The Developmental Conditions Of Toddlers Using KPSP.The Results Of The Study Showed That There Was A Relationship Between Nutritional Status And The Development Of Toddlers In The Candi Sidoarjo Health Center Work Area (P-Value <0.05).. Children Who Receive Adequate Nutrition Will Have Healthy Immune Systems, Optimal Growth And Development, And Improved Learning And Interpersonal Skills.On The Contrary, Children With Nutritional Problems Such As Undernutrition Or Overnutrition Can Experience Various Problems In Their Development. Parents And The Community Must Pay Attention To The Nutritional Status Of Children Under The Age Of Five And Pay Attention To Providing Sufficient And Balanced Nutrition.